Chemical Transformations during Aging of Zerovalent Iron Nanoparticles in the Presence of Common Groundwater Dissolved Constituents - Reinsch, Brian C; Forsberg, Brady; Penn, R. Lee; Kim, Christopher S; Lowry, Gregory V (Environmental science & technology, 2010)
Nanoscale zerovalent iron (NZVI) that was aged in simulated groundwater was evaluated for alterations in composition and speciation over 6 months to understand the possible transformations NZVI could undergo in natural waters. NZVI was exposed to 10 mN of various common groundwater anions (Cl−, NO3 −, SO4 2−, HPO4 2−, and HCO3 −) or to dissolved oxygen (saturated, ∼9 mg/L). Fresh and exposed NZVI samples, along with Fe-oxide model compounds, were then analyzed using synchrotron radiation X-ray absorption spectroscopy (XAS) to yield both relative oxidation state, using the X-ray absorption near edge structure (XANES), and quantitative speciation information regarding the types and proportions of mineral species present, from analysis of the extended X-ray absorption fine structure (EXAFS). Over 1 month of aging the dissolved anions inhibited the oxidation of the NZVI to varying degrees. Aging for 6 months, however, resulted in average oxidation states that were similar to each other regardless of the anion used, except for nitrate. Nitrate passivated the NZVI surface such that even after 6 months of aging the particles retained nearly the same mineral and Fe0 content as fresh NZVI. Linear least-squares combination fitting (LCF) of the EXAFS spectra for 1 month-aged samples indicated that the oxidized particles remain predominantly a binary phase system containing Fe0 and Fe3O4, while the 6 month aged samples contained additional mineral phases such as vivianite (Fe3(PO4)2·8H2O) and iron sulfate species, possibly schwertmannite (Fe3+ 16O16(OH,SO4)12−13·10−12H2O). The presence of these additional mineral species was confirmed using synchrotron-based X-ray diffraction (XRD). NZVI exposed to water saturated with dissolved oxygen showed a rapid (<24 h) loss of Fe0 and evolved both magnetite and maghemite (γ-Fe2O3) within the oxide layer. These findings have implications toward the eventual fate, transport, and toxicity of NZVI used for groundwater remediation.